Colloidal synthesis of flower-like Zn doped Ni(OH)2@CNTs at room-temperature for hybrid supercapacitor with high rate capability and energy density. (10th May 2022) - Ren, Xiaohe; Gan, Ziwei; Sun, Mengxuan; Fang, Qisheng; Yan, Yijun; Sun, Yongxiu; Huang, Jianan; Cao, Baobao; Shen, Wenzhong; Li, Zhijie; Fu, YongQing
Highlights: Flower-like Zn doped Ni(OH)2 @CNTs (ZNC) was in-situ synthesized by a colloidal method at room temperature. ZNC shows a high specific capacity of 726.5 C g -1 at 1 A g -1 and maintains 72.9% at 10 A g -1 . The energy density of ZNC//AC hybrid supercapacitor (HSC) is 51.3 Wh kg -1 at the power density of 409.6 W kg -1 . After 50, 000 cycles, the energy density of ZNC//AC HSC maintains 29.33 Wh kg -1 at 16.5 kW kg -1 . After 50, 000 cycles, the capacity of the HSC becomes 115.8% of its initial value. Abstract: Transition metal oxides and hydroxides are typically applied as electrode materials for supercapacitors, but it is often difficult to achieve both their high power density and energy density simultaneously. Herein, electrodes of flower-like Zn doped Ni(OH)2 combined with carbon nanotubes (i.e., Zn doped Ni(OH)2 @CNTs) were in-situ synthesized using a colloidal synthesis method at room-temperature, assisted by cetyltrimethyl ammonium bromide (CTAB) and NaBH4 . This electrode exhibits an excellent electrochemical performance, achieving a high specific capacity of 750.5 C g -1 at 0.5 A g -1 and maintaining 72.9% of its initial value when the current density is increased from 1 A g -1 to 10 A g -1 . A hybrid supercapacitor (HSC) assembled using the Zn doped Ni(OH)2 @CNTs as the positive electrode and an active carbon as the negative electrode exhibits a capacity of 201.7 C g −1 at 1 A g -1 and an energy density of 51.3 Wh kg -1 at a power density of 409.6 W kg -1 . After running for 50, 000 cycles at a current density of 6 A g -1, the capacity of the HSC becomes 115.8% of its initial value. Moreover, this HSC maintains a high energy density of 29.33 Wh kg -1 at a high power density of 16.5 kW kg -1 after cycling for 50, 000 times, which indicates its suitability for energy storage applications. Graphical abstract: Image, graphical abstract